2018
DOI: 10.3390/geosciences8090332
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Crude Oil on Mechanistic Detachment Rate Parameters

Abstract: Iraqi soil contamination greatly influenced soil detachment. Previous researchers have not been able to predict the influence of crude oil soil contamination on either the mechanistic dimensional detachment parameter b0 or the threshold parameter b1 of the mechanistic detachment model (Wilson model). The aims of this research were (1) to investigate the influence of crude oil on deriving Wilson model parameters, b0 and b1, with two setups at different scales and different soil moisture contents and (2) to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The software recommended both Tukey test method and student-Newman-Keuls method to test all pairwise comparisons of the mean responses to different treatment groups. Thus, in this study, pairwise comparisons of t-tests are calculated for both observed and predicted flow rates using the Tukey test method and student-Newman-Keuls method, which revealed a significant difference compared to ANOVA with a significance level of α = 0.05 [25].…”
Section: Discussionmentioning
confidence: 99%
“…The software recommended both Tukey test method and student-Newman-Keuls method to test all pairwise comparisons of the mean responses to different treatment groups. Thus, in this study, pairwise comparisons of t-tests are calculated for both observed and predicted flow rates using the Tukey test method and student-Newman-Keuls method, which revealed a significant difference compared to ANOVA with a significance level of α = 0.05 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Wilson (1993aWilson ( , 1993b proposed a mechanistic detachment model to provide a general framework for studying soil and fluid characteristics [10,11]. The advantage of the Wilson model over the over-shear stress model is that the factors affecting erosion can be considered and evaluated in greater depth; this has been studied extensively by related scholars, incorporating factors such as turbulence, roughness, seepage forces, material soil orientation, root effects, and negative pore water pressure effects into the Wilson model [12][13][14][15][16]. The Wilson model was based on the balance of all the forces and moments driving and resisting detachment that would be preferred for modeling the range of possible environmental conditions, which is expressed as:…”
Section: Introductionmentioning
confidence: 99%
“…For the parameters in the scour model, it is also vital to determine their relationship with soil parameters. Hasan and Al-Madhhachi (2018) investigated the effect of crude oil on erosion parameters (b 0 and b 1 ) [13]. For clean soil and polluted soil, parameter b 1 increases with increasing water content.…”
Section: Introductionmentioning
confidence: 99%